2017
DOI: 10.18240/ijo.2017.04.18
|View full text |Cite
|
Sign up to set email alerts
|

Association of choroidal thickness with early stages of diabetic retinopathy in type 2 diabetes

Abstract: CT decreased significantly in the NDR and mild/moderate NPDR eyes compared with the control eyes. Age is significantly associated with SFCT in the diabetic patients. Diabetic choroidopathy may be present before clinical retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
18
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
5
18
0
Order By: Relevance
“… 39 Regatieri et al, 10 however, reported a thinner CT in patients with diabetic macular edema or treated proliferative DR compared with normal subjects. Vujosevic et al, 11 Esmaeelpour et al, 12 , 13 Querques et al 14 and Shen et al 15 also demonstrated that CT decreases in diabetic eyes with clinical signs of DR compared with controls.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“… 39 Regatieri et al, 10 however, reported a thinner CT in patients with diabetic macular edema or treated proliferative DR compared with normal subjects. Vujosevic et al, 11 Esmaeelpour et al, 12 , 13 Querques et al 14 and Shen et al 15 also demonstrated that CT decreases in diabetic eyes with clinical signs of DR compared with controls.…”
Section: Discussionmentioning
confidence: 94%
“… 9 EDI-OCT dramatically increases image resolution of the choroid by decreasing signal strength posterior to the retinal pigment epithelium. Although many authors have reported a decrease in choroidal thickness (CT) among diabetic patients, 10 15 there are some discordant studies. 7 , 16 , 17 …”
Section: Introductionmentioning
confidence: 99%
“…Choroidal changes in diabetic patients might play an important role in the development of DR, because the choroid is responsible for supplying blood to the outer retinal layer 10 . Several choroidal changes have been described in diabetic patients, but reports on CT in such eyes are discrepant.…”
Section: Discussionmentioning
confidence: 99%
“…Several choroidal alterations in diabetic patients have been described in the literature 10 14 . Recently there has been a focus on CT, which differs significantly from that of healthy patients; however, inconsistent results have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation